Session 1: The evolution and development of the multidisciplinary team approach: USA, European and UK experiences – what can we do better?. (May 2018) - Wale, A.; Wexner, S. D.; Saur, N. M.; Massarotti, H.; Laurberg, S.; Kennedy, E.; Rockall, A.; Sebag‐Montefiore, D.; Brown, G.
Abstract: The process of determining the best treatments that should be offered to patients with newly diagnosed colon and rectal cancer remains highly variable around the world. The aim of this expert review was to agree the key elements of good quality preoperative treatment decision making.